Trends of primary Schools’ Conflict Resolution as Peace Education: A Bibliometric Analysis - Wahyuningsih, Yona; Maftuh, Bunyamin; Sapriya, Sapriya; Darmawan, Deni (Indonesian Research Journal in Education |IRJE|, 2024)
This research aimed to analyze computational mapping on bibliometric data "Primary School Conflict Resolution as Peace Education" from the Google Scholar database via Publish or Perish software. Based on the research results, there were 950 relevant articles published from 2013 to 2023. The research results focused on three areas: the term conflict resolution, the term peace education, and the term primary school by showing the development of the number of articles, which experienced a significant increase from 2013 until 2017. The development of this research is starting to be published less frequently, as can be seen from the drastic decline from 2021 to 2023. Therefore, it can be said to be experiencing a decline. Through VOSviewer, this research analyzes many published articles related to the topic. The impact of this review is a starting point for conducting research on related topics in the future.